2018
DOI: 10.1021/acsami.8b11449
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibers Regulate Single Bone Marrow Stem Cell Osteogenesis via FAK/RhoA/YAP1 Pathway

Abstract: Understanding cell-material interactions is a prerequisite for the development of bio-inspired materials for tissue regeneration. While nanofibrous biomaterials have been widely used in tissue regeneration, the effects of nanofibrous architecture on stem cell behaviors are largely ambiguous because the previous biomaterial systems used for nanofiber-cell interactions could not exclude the interference of cell-cell interactions. In this study, we developed a unique micropatterning technology to confine one sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 41 publications
4
45
0
Order By: Relevance
“…Nanomaterials, which could exert certain regulatory function in vivo, had obtained accumulated evidence of their roles in osteogenic differentiation [11][12][13]. Exosomes represent a promising type of nanomaterials from which miRNAs can be isolated [14].…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials, which could exert certain regulatory function in vivo, had obtained accumulated evidence of their roles in osteogenic differentiation [11][12][13]. Exosomes represent a promising type of nanomaterials from which miRNAs can be isolated [14].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that curcumin by reversing activity of the Wnt/β‐catenin signaling modulated osteogenic differentiation of the MSCs while inhibited by H 2 O 2 36 . In addition, the literature showed that several signal pathways induced by nanofibers to the stem cells during osteogenesis while cultured on the nanofibrous scaffolds as an artificial ECM including, FAK/RhoA/YAP1 in bone marrow stem cells, 37 Wnt/β‐catenin in ADSCs, 38,39 and MAPK signaling in other stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…8 BMSCs have the self-renewal capacity and multidirectional differentiation potential, and they can differentiate into multiple cell lineages, including osteoblasts, chondrocytes, and adipocytes under specific conditions. 9 They also possess the immune-modulatory functions and can secret some paracrine factors which participate in endogenous tissue regenerative capacity. Current studies suggest that these characteristics make BMSC an ideal cell source for tissue engineering of cell-based therapies for many degenerative diseases including OP.…”
mentioning
confidence: 99%